The tale of genji - Shikibu, Murasaki (Alfred A. Knopf, 2006)
The Tale of Genji was written in the eleventh century by Murasaki Shikibu, a lady of the Heiancourt. It is universally recognized as the greatest masterpiece of Japanese prose narrative, perhaps the earliest true novel in the history of the world.